Niveles semánticos de las representaciones sociales de la inmigración subsahariana. Los sucesos de Ceuta y Melilla según ABC - Medina Bravo, Pilar; Concepción Sepúlveda, Luis Gilberto; Rodrigo Alsina, Miguel (Estudios sobre el Mensaje Periodístico, 2008)
From the contributions of Teun van Dijk, this work studies the representations of sub-Saharan immigrants in the media coverage elaborated by ABC on incidents over the fences of Ceuta and Melilla between September and October 2005. It underlines a stereotyped representation of the actors, information sources and circumstances that give order to a preformed script. This closed and fixed deposition, sustained by guidelines of interpretation shared by journalists and readers, will depict the immigrant as a preconceived mold subject to serialization. ABC sets, in addition, a symbolic order in which foreign people are no longer valid speakers capable of self-meaning. Their presence in the story becomes of literature kind at time that’s dependant of others account of their actions.
Keywords: Immigration; Sub-Saharan; Press; Spain